The impact of colonial legacies on service delivery in Zimbabwe's local authorities : the case of Mutare Rural District Council - Marembende, Tinotenda Prince (Midlands State University, 2020)
This research reviewed the challenges that are posed by the inherited colonial legacies towards the sustainable service delivery in the Mutare Rural District Council. The success of Local Authorities lies in the ability to bring about sustainable service delivery in their respective areas of jurisdiction in a country riddled with the effects of colonial legacies. This in turn enhances the much sought for socio-economic development throughout the country. For Rural Local Authorities (RLAs), service delivery is of paramount importance in a bid to improve the quality of life in Zimbabwe’s rural areas and correct the developmental imbalances against the inherited colonial legacies that may hinder progress today. As such, the research hypothesized the colonial legacies as what most RLAs are striving to curb. Not only is it about the poor public policies in place but other challenges faced by RLAs which may include the crisis of local governance, rampant corruption, low institutional capacity, poor financial management and low revenue base. This research is an investigation into the impacts of colonial legacies on the operations of Local Authorities and how effective they are in the enhancement of sustainable service delivery as well as the alternative strategies they employ in enhancing service delivery. Special reference will be given to Mutare Rural District Council.